National education policy: Implementation of Artificial Intelligence in higher education - 'Alam, Ghasa Faraasyatul; Purnawirawan, Okta; Herlambang, Admaja Dwi; Batita, Maurish Sofie Rahmi (Journal of Smart Education and Learning, 2025)
The application of Artificial Intelligence (AI) in higher education continues to experience rapid development along with the digital transformation in various aspects of life. Universities are required to adapt to technological advances in order to strengthen institutional competitiveness and reputation. This study aims to analyze national education policies in the digital era related to the implementation of AI in universities to build institutional reputation. The methods used are policy analysis and literature study, with the help of Publish or Perish software for searching scientific articles, and VOSviewer for visualization and bibliometric analysis. Results of the study show that national education policy has created a basis for the use of digital technologies such as AI by encouraging adaptive learning, increasing administrative efficiency, and adjusting education services. However, several challenges still hinder the implementation of AI in higher education. To support digital transformation in education, the government, universities, and the industrial sector must work together by creating a supportive ecosystem. Implementation of AI use in higher education can change the paradigm of digital-era education in Indonesia into a more inclusive, responsive, and data-based system.